Pengaruh Etika Kerja dan Komunikasi Terhadap Kinerja Karyawan CV. Piramida Engineering Consultant - Rasty Yulia; Hertya Andriani (LPPM Politeknik Pratama, 2026)
The main problem in the following research is the implementation of employee performance at CV. Piramida Engineering Consultant is classified as inadequate. The purpose of this research is to determine the impact of declining work ethics and communication on employee performance at CV. Piramida Engineering Consultant. Which variables have the greatest impact on employee performance at CV. Piramida Engineering Consultant. This type of research is quantitative using an associative research approach whose purpose is to test the correlation between two or more variables. The data collection methods used are questionnaires, reference searches, documentation, and supported actual facts. The analysis method used in this writing is multiple regression analysis using the SPSS Version 22 program which is used to explain a number of independent variables (X) on the dependent variable (Y). the results of the research show that work ethics have a significant and positive impact on employee performance and communication has a significant and positive impact on employee performance.